TYPES OF MOTHER LANGUAGE LESSONS ACCORDING TO THE PURPOSE (Academia Science Repository, 2023)
The native language lessons are divided into four types according to the purpose: teaching and strengthening of new material, repeating what has been learned and creating skills, lessons summarizing knowledge and skills, and testing knowledge and skills.